IMPLEMENTASI KARUNIA-KARUNIA ROH KUDUS BERDASARKAN 1 KORINTUS 12:8-10 - Yarni Harefa; Gregorius Suwito; Tri Astuti (JOURNAL of THEOLOGICAL STUDENTS, 2020)
The gifts of the Spirit are gifts that God has given to his church so that in every ministry there is power in it. All the gifts that God has given to fulfill the Great Commission are already in the midst of His people. The gifts only need to be found. The gifts of the Spirit are not the same, each person receives according to the measure of the gift of Christ. The purpose of the gifts of the Spirit is to build up everyone. Therefore these gifts must be used properly and regularly.